Legal ratio of regulations on the rehabilitation of inmates in correctional institutions as an instrument for reducing recidivism in drug-related crimes - Abd Razak Musahib; Made Warka; Frans Simangungsong (Technium Social Sciences Journal, 2026)
The ratio legis of rehabilitation for narcotics recidivists is based on the idea that narcotics abuse is a health and social problem that requires special handling, not merely criminal punishment. Rehabilitation is positioned as an instrument to correct behavior, treat addiction, and eliminate criminogenic factors that trigger recidivism. There is a gap between the ratio legis of rehabilitation regulations and their implementation in the field. Therefore, it is important to conduct a study on rehabilitation regulations for drug recidivists to assess the effectiveness of existing regulations, analyze implementation constraints, and formulate more appropriate policy recommendations to reduce drug recidivism rates. This study uses a normative legal research method. The results of the study show that the effectiveness of rehabilitation as an instrument for reducing recidivism is highly dependent on the synchronization between regulations, implementation in prisons, and post-release support.